Lung surgery in interstitial lung disease—a safe and useful procedure? - Kolb, Martin; Shargall, Yaron (Journal of Thoracic Disease, 2013)
The group of interstitial lung diseases (ILD) includes a wide spectrum of disorders with variable clinical presentation, treatment response and prognosis. Idiopathic pulmonary fibrosis (IPF) is by far the most dismal disease in this group, with a median survival time of just 3-4 years (1). The diagnostic criteria for IPF are based on exclusion of any other cause for ILD by thorough clinical history, and a typical radiographic image revealing a so-called usual interstitial pneumonia (UIP) pattern in a high resolution computed tomography (HRCT) (2).